1961
DOI: 10.1084/jem.113.6.1013
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Streptococcal Infections

Abstract: It has been found by immunoelectrophoresis, that Group A streptococci release at least 20 distinct extracellular antigens in human tissues, as judged by naturally occurring antibodies present in normal pooled human gamma globulin. Several of these precipitin arcs have been identified with streptococcal antigens previously purified by electrophoresis and chromatography. Human gamma globulin, as well as several rheumatic fever sera, were shown to be remarkably potent in antistreptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1963
1963
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For more than 40 years, it has been known that patients with GAS infections produce antibodies to a large number of extracellular proteins (16)(17)(18)(19)(20)24), but most of these antigens have not been identified. Availability of genome sequences has permitted virulence factors and therapeutic agent candidates to be identified very rapidly by comparative genomics and other postgenomic methods (2,3,14,21,24,32,35,37).…”
Section: Discussionmentioning
confidence: 99%
“…For more than 40 years, it has been known that patients with GAS infections produce antibodies to a large number of extracellular proteins (16)(17)(18)(19)(20)24), but most of these antigens have not been identified. Availability of genome sequences has permitted virulence factors and therapeutic agent candidates to be identified very rapidly by comparative genomics and other postgenomic methods (2,3,14,21,24,32,35,37).…”
Section: Discussionmentioning
confidence: 99%
“…~ These preparations were made according to methods previously described (8)(9)(10)(11)(12) and had been used in other studies (4)(5)(6). The Group A toxin consisted entirely of protein and had a titer of 160,000 hemolytic units (HU) per milligram of dry weight; the Group C material, which was 67% protein, had a tlter of 40,000 HU/mg.…”
Section: Methodsmentioning
confidence: 99%
“…The latter all showed "reactions of identity" with each other. However, when proteinase assays were carried out, it was found that the first peak ( I and 11) was primarily proteinase precursor (1,580 total units/mg., 6 percent in the active state) while the second peak (111) was largely active proteinase (1,580 total units, SO-100 percent in the active state). In spite of this fact, no spurs were noted here, and in other similar instances, between these two precipitin bands.…”
Section: Studies With the Proteinase Precursor System (Peak Ill)mentioning
confidence: 99%
“…An immunoelectrophoretic test of crude culture supernate concentrates of group A streptococcal growth against human gamma globulin revealed at least 20 extracellular products which must have been secreted in vivo. 6 An example of these findings is shown in FIGURE 1, a1 and a2, in which two different culture concentrates from the C203S group A streptococcal strain and a group C streptococcal concentrate were separated electrophoretically, and then exposed to the antibodies in pooled human gamma globulin. In FIGURE l b is shown a diagrammatic representation of the results obtained with the crude streptococcal concentrate which was used as a reference standard system.…”
mentioning
confidence: 99%